(untitled) (ModaPalavra e-periódico, 2024)
Minimalism is a theme on the rise in consumer literature, especially when it involves fashion and minimalist aesthetics. Despite this, there are few studies dedicated to discussing what reactions the minimalist aesthetics may produce on the perceptions of others about minimalists as individuals. With this essay, we fill this gap by discussing what image minimalist aesthetics conveys about people who adopt a minimalist clothing style. We discuss, therefore, how minimalists may be perceived as more competent and less warm people in the eyes of others, in addition to being able to convey an image of rationality in decision making rather than feelings. Finally, this essay opens up the possibility for a wide range of future studies on minimalism in consumption.